Care: Intersections of scales, inequalities and crises. (July 2018) - Williams, Fiona
This article develops an understanding of how and why care is a central issue for personal relationships and for global sustainability and justice. Three approaches inform the synthetic analytical framework: intersectionality; the transnational political economy of care within the context of global crises of care, finance, environment and migration; and the ethics of care. The article applies these to an analysis that can account for the multidirectional dynamics of care from micro to meso to macro scales, as well as to the salient intersections of categories within each of these levels. It argues for a care-ethical approach to global social justice and sustainability that recognizes the centrality of care and interdependence to everyday life.